2022
DOI: 10.3390/agronomy12040890
|View full text |Cite
|
Sign up to set email alerts
|

Does Straw Returning Amended with Straw Decomposing Microorganism Inoculants Increase the Soil Major Nutrients in China’s Farmlands?

Abstract: Although straw-decomposing microbial inoculants (SDMI) are capable to generally promote the fertility of straw-amended soils, their impact on the release of individual soil major nutrients remains controversial. Additionally, the combined effects of SDMI and environment/management on various forms of nutrients remain poorly documented. To fill these research gaps, we conducted a meta-analysis study using 1214 paired observations from 132 field trials in China. Our results showed that SDMI significantly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…In addition, organic acids segregated by BSCs could contribute to mineral bio-weathering, thus solubilizing P compounds (Sokol et al 2022;Zubiri et al 2022). Nutrients released from the litter of BSCs are the most relevant sources of humus formation, and could improve soil major nutrients (He et al 2022;Liu et al 2022;Sokol et al 2022;Tian et al 2022b;Tonello et al 2022;Turan et al 2019). It has been found that BSCs can boost surface soil fertility, especially in terms of the TN, TP and OC contents of soils in deserts and mine dust (Deng et al 2020;Gao et al 2018;Karimi et al 2022;Lucieer et al 2014;Mager and Thomas 2011;Nyenda et al 2019;Tian et al 2022b;Wang et al 2022a, b;Wu et al 2001;Zhang et al 2012;Zubiri et al 2022).…”
Section: Effect Of Crevice Density On Major Soil Nutrient Contentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, organic acids segregated by BSCs could contribute to mineral bio-weathering, thus solubilizing P compounds (Sokol et al 2022;Zubiri et al 2022). Nutrients released from the litter of BSCs are the most relevant sources of humus formation, and could improve soil major nutrients (He et al 2022;Liu et al 2022;Sokol et al 2022;Tian et al 2022b;Tonello et al 2022;Turan et al 2019). It has been found that BSCs can boost surface soil fertility, especially in terms of the TN, TP and OC contents of soils in deserts and mine dust (Deng et al 2020;Gao et al 2018;Karimi et al 2022;Lucieer et al 2014;Mager and Thomas 2011;Nyenda et al 2019;Tian et al 2022b;Wang et al 2022a, b;Wu et al 2001;Zhang et al 2012;Zubiri et al 2022).…”
Section: Effect Of Crevice Density On Major Soil Nutrient Contentsmentioning
confidence: 99%
“…Furthermore, in the process of ecological restoration, plant community structure can be optimized with time, and thus, more litter is input into soils (Deng et al 2020;Feng et al 2011;Nyenda et al 2019;Zhao et al 2015). The increase in litter directly transports organic matter and nutrient elements into the soil, resulting in the increase in major soil nutrients with time (Feng et al 2011;He et al 2022;Li et al 2018b;Liu et al 2022;Sokol et al 2022;Tian et al 2022b;Tonello et al 2022;Zhao et al 2015). Nevertheless, in our study, OC, TN and TP contents in soils on RCSs vary irregularly, possibly attributed to the interaction between the contents in the grains trapped from the slope soils and air, BSC biomass accumulation, decomposition of organic matter, erosion intensity by water and air, etc.…”
Section: Nonlinear Variation In Properties Of Soils With Famentioning
confidence: 99%
See 1 more Smart Citation
“…Both controlled and field experiments suggest that supplementation with controlled release N fertilizer increases cereal crop morphology traits, gas exchange attributes, and soil inorganic N and organic C content over the reproductive period 16‐18 . Short‐term straw returning fertilization effects on crop yields are likely to reduce because of the uncertainty in the quality and quantality of straw decomposition to nutrients over the changing growing season 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Short-term straw returning fertilization effects on crop yields are likely to reduce because of the uncertainty in the quality and quantality of straw decomposition to nutrients over the changing growing season. 19,20 Conventional N urea application practices (such as multiple application and subsurface placement) enhance leaf development, N allocation to harvest organs and decrease the N losses to environment. 21 However, lack of effective labor and appropriate machinery often limit the application of these practices in paddy soil.…”
Section: Introductionmentioning
confidence: 99%